Road freight transport across a fixed Fehmarn Belt link - Jespersen, Per Homann (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
A fixed link between Denmark and Germany was agreed upon by the Danish and German governments on June 30 2007. The bridge (probably preferred to a tunnel) will cross the Fehmarn Belt between Rødby in Denmark and Puttgarden on the island of Fehmarn, in Schleswig-Holstein in Germany, a span of 20 kilome- tres. The bridge will be finished by 2017. The agreement was reached after more than 10 years period of investigations and negotiations on technical, environmental and not least financial aspects. Different models from private financing and ownership over a number of PPP’s (Public- Private Partnership) were reviewed until a full state financed model was agreed upon – a model where the Danish State will pay, build and operate the bridge. The German contribution will be the land connections on the German side – around 40 kilometres of highway to connect the bridge with the ‘Autobahn’- system and the upgrading and electrification of the 90 kilometres of single rail track from Puttgarden to Lübeck. If railway traffic seven years after the opening of the bridge (i.e. 2024) exceeds a certain limit (80 trains a day has been mentioned) the Germans will start constructing a second rail track. On Danish soil the construction will mainly be an upgrading of the rail from Copenhagen to Rødby. Between Copenhagen and Ringsted new track is already being planned, and from Ringsted to Rødby the existing single, non-electrified track has to be doubled and electrified. However, across the old 3,5 kilometre Storestrømsbro there will only be single track. The decision to build a fixed link is of course founded on thorough traffic forecasts (Wätjen 2003) and economic calculations (Sund & Bælt Holding A/S 2003) and has by the Danish government been characterised as a ‘very good business investment’, that will not burden the public finances (Prime Minister Anders Fogh Rasmussen at a press briefing, February 20, 2007). In this paper the impacts of a fixed link on road freight transport has been studied. The results differ somewhat from what has been found in the traffic forecast studies, and this divergence is being discussed.